2021
DOI: 10.1038/s41467-021-25149-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural descriptor for enhanced spin-splitting in 2D hybrid perovskites

Abstract: Two-dimensional (2D) hybrid metal halide perovskites have emerged as outstanding optoelectronic materials and are potential hosts of Rashba/Dresselhaus spin-splitting for spin-selective transport and spin-orbitronics. However, a quantitative microscopic understanding of what controls the spin-splitting magnitude is generally lacking. Through crystallographic and first-principles studies on a broad array of chiral and achiral 2D perovskites, we demonstrate that a specific bond angle disparity connected with asy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(167 citation statements)
references
References 60 publications
6
141
2
Order By: Relevance
“…This implies that the enhanced asymmetric factor of CPPL (g CPPL ) in chiral 2D OIHPs results from the facilitated chirality transfer phenomena rather than the Rashba effect itself (induced by the large SOC of OIHPs). Very recently, the Mitzi group found that the Rashba-Dresselhaus spin-splitting is a consequence of the chirality transfer phenomena 52 . Based on their findings and experimental results, the other effects such as the Rashba effect or Rashba-Dresselhaus spin-splitting (whether it occurs or not), which might contribute to the measured CPPL, cannot be explained separately.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the enhanced asymmetric factor of CPPL (g CPPL ) in chiral 2D OIHPs results from the facilitated chirality transfer phenomena rather than the Rashba effect itself (induced by the large SOC of OIHPs). Very recently, the Mitzi group found that the Rashba-Dresselhaus spin-splitting is a consequence of the chirality transfer phenomena 52 . Based on their findings and experimental results, the other effects such as the Rashba effect or Rashba-Dresselhaus spin-splitting (whether it occurs or not), which might contribute to the measured CPPL, cannot be explained separately.…”
Section: Resultsmentioning
confidence: 99%
“…7,31 A particular application of inorganic layer asymmetry relates to Rashba−Dresselhaus spin-splitting in 2D perovskites, which may play an important role in controlling spin-related properties. 31,32 The optical properties of all 2D perovskites in this work were examined via UV−vis absorption spectroscopy (Figure 4a,c). While the pure chiral perovskite (i.e., with S/R-MePEA) exhibits a relatively blue-shifted exciton peak, the achiral perovskite (i.e., C4A) exhibits a red-shifted peak, with the exciton peak for the mixed-cation perovskite falling in between.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Fundamentally, the PbBr 6 octahedra tilting distortions arise from a complex interplay of charge-density, steric, and space-filling requirements, as well as specific hydrogen bonding interactions that couple the inorganic and organic sublattices. Chiral spacer cations always necessitate a chiral Sohncke space group to describe the overall perovskite structure; however, the degree of chirality (i.e., inversion and mirror asymmetry) in the isolated inorganic layers depends on the type and extent of specific bond angle distortions. , In the pure chiral perovskite with P 2 1 2 1 2 1 global space group, the inorganic framework comprises effectively two inorganic layers, each of which is nominally noncentrosymmetric with a P2 1 layer-symmetry (as determined by PLATON; see the Supporting Information for details) because of irregular tilting distortion of neighboring PbBr 6 octahedra within any given layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For systems not including alkali cations, the authors have found computationally optimized geometries in close agreement (1% or better) with experimentally determined counterparts. [ 25,43–46 ] This correction is defined as a sum over pairwise atomic interactions. Importantly, the vdW radius Rfree0 of each element enters the TS formulation.…”
Section: Methodsmentioning
confidence: 99%